Effect of the B4C particles on the brazed joints of SiC ceramics and 2219 aluminum alloy. Issue 1 (22nd November 2022) - Li, Xianfen; Cai, Kai; Teng, Peng; Hua, Peng; Cheng, Huimin; Zhou, Wei
Abstract: A two‐step process, including the premetallization of the SiC ceramic by Ag‐26.7Cu‐4Ti+B4 C and the followed brazing with the Al‐based filler alloy, was developed to join 2219 aluminum alloy and the metallized SiC. The influence of metallization temperature and the B4 C addition on the microstructure and mechanical properties of the joint was analyzed. The reaction products of Ti and B4 C were detected in the brazing seam, such as Ti2 B, TiC and graphite. With increasing of metallization temperature and B4 C addition content, the shear strength of joint first increased and then decreased. The joint shear strength reached 14.0 MPa when SiC metallized with Ag‐26.7Cu‐4Ti+1%B4 C at 930°C for 10 min, which showed that appropriate addition of B4 C in Ag‐26.7Cu‐4Ti metallization layer could regulate the coefficient of thermal expansion difference between 2219 aluminum alloy and SiC to relieve the residual stress and improve the shear strength of their brazed joint.